2023
DOI: 10.54536/ajet.v1i4.1089
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of Educational Games Using Lumi Education in General Biology 1 for STEM Students: Basis for Recommended Supplementary Teaching Materials

Abstract: This study aimed to assess the perceived effectiveness of the educational games and the overall performance of the students after it was introduced to them. A descriptive-comparative method of research was utilized. Respondents of this study were twenty-six (26) Grade-12 STEM students. Researcher-made validated questionnaire based on a 5-point Likert scale was used for data collection. The findings of this study revealed that the contents used for educational games were about the cell cycle and cell membrane. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…This is supported by other research that found a positive correlation between student engagement and achievement (Ainley & Ainley, 2011;Dotterer & Lowe, 2011;Lam, et al, 2014). The study of Sumandal (2023) showed that student's motivation, interest, and cooperation increased using educational games. Similarly, mobile-supported self-learning modules enhances tsusents' oral communication skills (Santos, 2023).…”
Section: Literature Reviewsupporting
confidence: 69%
“…This is supported by other research that found a positive correlation between student engagement and achievement (Ainley & Ainley, 2011;Dotterer & Lowe, 2011;Lam, et al, 2014). The study of Sumandal (2023) showed that student's motivation, interest, and cooperation increased using educational games. Similarly, mobile-supported self-learning modules enhances tsusents' oral communication skills (Santos, 2023).…”
Section: Literature Reviewsupporting
confidence: 69%
“…Data revealed that in the latter school years, STEM students perceived improvement in the overall pedagogical methods applied by their teachers. Existing literatures revealed that such privileges were evident in terms of competent use of online resources and collaboration tools, recalibrating lessons to most essential competencies required for STEM graduates, applying gamification in lessons and assessments (i.e., Kahoot, Quizizz), enriched and relevant learning modules, reasonable due dates, doable workplans, and reducing workload to course requirements aligned to STEM learning Sumandal, 2023;Vallespin & Prudente, 2022). Providing creative and innovative practical exercises and enthusiastic teaching in Chemistry and other Science subjects was an important recommendation for STEM teachers (Mecida et al, 2023).…”
Section: School-based Assistancementioning
confidence: 99%
“…The lack of qualified Physics teachers, lack of textbooks and Physics teaching equipment, and congested curriculum were addressed to bring out the best in Physics education. Sumandal (2023) All these materials were found to be effective in improving students' academic performance in Physics. Research findings proved that an interactive teaching strategy stimulating students' interest can improve Physics teaching and learning.…”
Section: Literature Reviewmentioning
confidence: 99%